2017
DOI: 10.1111/dar.12473
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol consumption by breastfeeding mothers: Frequency, correlates and infant outcomes

Abstract: Low level drinking during breastfeeding is not linked with shorter breastfeeding duration or adverse outcomes in infants up to 12 months of age. [Wilson J, Tay RY, McCormack C, Allsop S, Najman J, Burns L, Olsson CA, Elliott E, Jacobs S, Mattick RP, Hutchinson D. Alcohol consumption by breastfeeding mothers: Frequency, correlates and infant outcomes. Drug Alcohol Rev 2017;00:000-000].

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
23
0
5

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 34 publications
1
23
0
5
Order By: Relevance
“…20 Alcohol passes quickly through to breastmilk at similar concentrations to maternal blood alcohol concentration 22 and reduces milk production. 21 Although drinking alcohol immediately after feeding minimizes ethanol exposure, 23 not all women use this technique, 16,20 and unpredictable infant feeding can mar such attempts. 20 Expressing and discarding "contaminated" breastmilk does not reduce ethanol concentration because this is related to maternal blood alcohol concentration.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…20 Alcohol passes quickly through to breastmilk at similar concentrations to maternal blood alcohol concentration 22 and reduces milk production. 21 Although drinking alcohol immediately after feeding minimizes ethanol exposure, 23 not all women use this technique, 16,20 and unpredictable infant feeding can mar such attempts. 20 Expressing and discarding "contaminated" breastmilk does not reduce ethanol concentration because this is related to maternal blood alcohol concentration.…”
mentioning
confidence: 99%
“…Whereas Little et al 34,35 found reduced psychomotor scores at 1 year in infants whose mothers drank alcohol while breastfeeding, the authors of more recent studies found no reduction in developmental scores. 16 Rat studies of nicotine intake during lactation have revealed reversible hypothyroidism in offspring. 36,37 Although hypothyroidism is associated with cognitive deficits in humans, 38 Gaworski et al 39 found that pups exposed to nicotine during pregnancy and lactation had intact learning and memory.…”
mentioning
confidence: 99%
“…Além disso, a maioria das mulheres que bebiam durante o aleitamento materno empregou estratégias de manejo para minimizar os efeitos potenciais do consumo de álcool, sendo a estratégia mais comum beber somente após alimentar o bebê. 7 Estudo realizado na França afirma que o consumo diário foi relatado por apenas 0,4% das mulheres que amamentavam. Nesse grupo, o consumo excessivo de álcool foi estimado em 6,8%.…”
Section: Frequência Do Uso De áLcool Durante a Amamentaçãounclassified
“…No entanto, há uma escassez de pesquisas usando dados em humanos e os resultados disponíveis foram inconsistentes. 7 Um estudo com 400 lactentes mostrou que o consumo regular de álcool por lactantes estava associado com menores escores de desenvolvimento em lactentes aos 12 meses de idade. 19 Em contraste, o mesmo autor, em um estudo subsequente 20 utilizando a mesma metodologia, mas em uma população diferente, não encontrou desfecho adverso no desenvolvimento de crianças expostas ao álcool durante a lactação.…”
Section: Os Efeitos Do áLcool Sobre O Lactenteunclassified
See 1 more Smart Citation